Exploring the Effect of Quality, Sophistication, Brand Image, and Marketing Mix on Willingness to Pay: Does Trust Mediate the Relationship? - Erilia Kesumahati; Jack Sen Lim; Edy Yulianto Putra (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2026)
The premium imported car market involves high perceived risk and intense competition, making consumer trust a key determinant of willingness to pay premium prices. While product quality, brand image, and marketing strategies are considered important drivers of consumer trust, empirical evidence explaining their combined effects particularly the role of sophistication remains limited in emerging markets. This study aims to examine the effects of product quality, service quality, sophistication, brand image, and marketing mix on trust and its impact on consumers’ willingness to pay for premium imported cars. This quantitative study involved 367 owners of premium imported cars in Indonesia, selected using purposive sampling. Data was analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS 3. The results show that product quality, service quality, brand image, and marketing mix have significant positive effects on trust, while sophistication does not have a significant effect on trust. In addition, trust significantly influences consumers’ willingness to pay premium prices. These findings highlight the importance of trust-building mechanisms through quality, branding, and marketing strategies. The study contributes to trust and signaling theory by clarifying which brand and marketing attributes effectively drive willingness to pay in the premium automotive context.